Rational Design of Carbon Nitride Photoelectrodes with High Activity Toward Organic Oxidations. Issue 50 (15th November 2022) - Pulignani, Carolina; Mesa, Camilo A.; Hillman, Sam A. J.; Uekert, Taylor; Giménez, Sixto; Durrant, James R.; Reisner, Erwin
Abstract: Carbon nitride (CN x ) is a light‐absorber with excellent performance in photocatalytic suspension systems, but the activity of CN x photoelectrodes has remained low. Here, cyanamide‐functionalized CN x ( NCN CN x ) was co‐deposited with ITO nanoparticles on a 1.8 Å thick alumina‐coated FTO electrode. Transient absorption spectroscopy and impedance measurements support that ITO acts as a conductive binder and improves electron extraction from the NCN CN x, whilst the alumina underlayer reduces recombination losses between the ITO and the FTO glass. The Al2 O3 |ITO : NCN CN x film displays a benchmark performance for CN x ‐based photoanodes with an onset of −0.4 V vs a reversible hydrogen electrode (RHE), and 1.4±0.2 mA cm −2 at 1.23 V vs RHE during AM1.5G irradiation for the selective oxidation of 4‐methylbenzyl alcohol. This assembly strategy will improve the exploration of CN x in fundamental and applied photoelectrochemical (PEC) studies. Abstract : Carbon‐nitride‐based photoelectrodes were produced by co‐deposition of a blend of cyanamide‐functionalized carbon nitride ( NCN CNx ) and indium tin oxide (ITO) nanoparticles on top of thin, alumina‐coated conducting FTO‐glass. The composite photoanodes display benchmark photocurrents with a range of different alcohol substrates, a low onset potential, and an incident photon‐to‐electron conversion efficiency (IPCE) up to 60 % at 350 nm.